Copper-catalysed photoinduced decarboxylative alkynylation: a combined experimental and computational study. Issue 19 (29th April 2020) - Mao, Yu; Zhao, Wenxuan; Lu, Shuo; Yu, Lei; Wang, Yi; Liang, Yong; Ni, Shengyang; Pan, Yi
Abstract : Redox-active esters (RAEs) as alkyl radical precursors have demonstrated great advantages for Cu-catalysed C–C bond formation. Abstract : Redox-active esters (RAEs) as alkyl radical precursors have demonstrated great advantages for C–C bond formation. A decarboxylative cross-coupling method is described to afford substituted alkynes from various carboxylic acids using copper catalysts CuCl and Cu(acac)2 . The photoexcitation of copper acetylides with electron-rich NEt3 as a ligand provides a general strategy to generate a range of alkyl radicals from RAEs of carboxylic acids, which can be readily coupled with a variety of aromatic alkynes. The scope of this cross-coupling reaction can be further expanded to aliphatic alkynes and alkynyl silanes using a catalytic amount of preformed copper-phenylacetylide. In addition, DFT calculations revealed the favorable reaction pathway and that the bidentate acetylacetonate ligand of the copper intermediate plays an important role in inhibiting the homo-coupling of the alkyne.